Finding the UV–Visible Path Forward: Proceedings of the Community Workshop to Plan the Future of UV/Visible Space Astrophysics. (12th June 2017) - Scowen, Paul A.; Tripp, Todd; Beasley, Matt; Ardila, David; Andersson, B.-G.; Apellániz, Jesús Maíz; Barstow, Martin; Bianchi, Luciana; Calzetti, Daniela; Clampin, Mark; Evans, Christopher J.; France, Kevin; et al.
Abstract: We present the science cases and technological discussions that came from the workshop titled " Finding the ultraviolet (UV)-Visible Path Forward " held at NASA GSFC 2015 June 25–26. The material presented outlines the compelling science that can be enabled by a next generation space-based observatory dedicated for UV–visible science, the technologies that are available to include in that observatory design, and the range of possible alternative launch approaches that could also enable some of the science. The recommendations to the Cosmic Origins Program Analysis Group from the workshop attendees on possible future development directions are outlined.